Calcitonin Gene-Related Peptide in Blind, Painful Eyes. Issue 3 (May 2020) - Godbout, Erin E.; Lau, Kevin W.; Adam, Alejandro P.; Wladis, Edward J.
Abstract : Purpose: To determine if calcitonin gene-related peptide (CGRP) is overexpressed in blind, painful eyes. Methods: This was a retrospective cross-sectional randomized control study conducted at a tertiary level hospital. Eight specimens of eyes enucleated by a single surgeon were included in the study. The control group patients underwent exenteration for cutaneous malignancy without intraocular involvement, while the case group was enucleated for management of blind, painful eye. Each eye was stained using immunohistochemistry for the expression of CGRP. Expression of CGRP was examined by counting the number of cells staining positive for CGRP in 5 consecutive ×40 fields in the choroid, iris, and cornea of each specimen. Results: The mean number of cells staining positively for CGRP in the choroid of blind, painful eye group was 45.5 (26.3) versus 5.5 (7.7) in nonpainful enucleated eyes. This difference was found to be statistically significant ( p = 0.016). Comparison of iris and cornea did not reach statistical significance. Expression of CGRP was compared using a paired t test. Conclusions: This study demonstrates that CGRP is overexpressed in the choroid of enucleated blind, painful eyes. Modulation of this protein may represent a meaningful, nonsurgical therapeutic strategy to addressing the blind, painful eye. Abstract : Calcitonin gene-related peptide is overexpressed in the choroid of enucleated blind, painful eyes.